A reusable wave-transparent thermal-insulation aerogel material and a preparation method thereof
Patent Information
- Application Number
- CN202410960906.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-17
AI Technical Summary
[0005]针对现有技术中气凝胶透波隔热材料难以重复使用的问题,本发明提供了一种可重复使用疏水气凝胶透波隔热材料及其制备方法,该方法制备得到的透波隔热气凝胶材料在500℃、2h的热处理10次后仍能保持良好的透波隔热性能
[0030]1、本发明所述的一种可重复使用透波隔热气凝胶材料的制备方法,采用原位法+表面修饰法制备具有超疏水性能的透波隔热气凝胶材料;原位法配方简单易调控,未增加繁杂的工艺步骤,使气凝胶材料具有疏水性的同时引入了耐高温的纳米无机氧化物氧化铈后续通过表面修饰法嫁接PFDTES,进一步提高疏水性和耐温性。两种方法结合使制得的气凝胶材料疏水效果可控,配方可控,疏水均匀性较好,材料内外部均具有超疏水性,同时使气凝胶耐温性能更佳,具有可重复使用性能。
Smart Images

Figure CN118754597B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel material technology, specifically relating to a reusable wave-transparent thermal insulation aerogel material and its preparation method. Background Technology
[0002] Aerogel materials, with their high thermal insulation efficiency and high wave transmission, are widely used in aerospace, weaponry, and other fields. The development of reusable spacecraft is an important direction for the aerospace industry, thus creating a demand for the reusability of aerogel materials.
[0003] Existing aerogel microwave-transparent thermal insulation composites typically maintain their excellent properties of high thermal insulation and high microwave transmission by replacing their surface hydrophilic groups through hydrophobic modification. There are two common methods for hydrophobic modification of aerogel materials: one is in-situ polymerization, which involves adding silanols containing hydrophobic groups to the sol-gel system, combining the sol with fibers, and then obtaining the hydrophobic aerogel microwave-transparent thermal insulation composite through gelation, aging, and supercritical drying processes; the other is surface post-treatment, also called surface modification, a commonly used surface modification process. Its key is to inertize the strongly polar -OH groups on the surface, thereby forming non-polar or weakly polar -OR groups (R being any aliphatic group), transforming the hydrophilic aerogel into a hydrophobic aerogel. However, most hydrophobic modifications use low surface energy organic hydrophobic agents, which can generally withstand temperatures below 400℃. When working in high-temperature environments for a long time, the organic matter will gradually decompose, reducing or eliminating the hydrophobic effect. When it absorbs moisture or comes into contact with water, the structure collapses and pulverizes, resulting in a serious decrease or even loss of wave transmission and heat insulation performance.
[0004] Therefore, reusable wave-transparent and heat-insulating aerogel materials have become an urgent need in the aerospace field. Summary of the Invention
[0005] To address the problem that existing aerogel wave-transparent thermal insulation materials are difficult to reuse, this invention provides a reusable hydrophobic aerogel wave-transparent thermal insulation material and its preparation method. The wave-transparent thermal insulation aerogel material prepared by this method can still maintain good wave-transparent thermal insulation performance after 10 heat treatments at 500℃ for 2 hours.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] A method for preparing a reusable microwave-transparent thermal insulation aerogel material includes the following steps:
[0008] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:(0.25-1):(3-4):(5-20):1.8×10 -3 3.6×10-2 Prepare the sol;
[0009] The silicon source is selected from one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and isopropyl orthosilicate.
[0010] The hydrophobic agent is selected from one of phenyltrimethoxysilane (PTMS), phenyltriethoxysilane (PTES), and methyltriethoxysilane (MTEOS);
[0011] The alcohols mentioned are selected from one of methanol, ethanol, isopropanol, n-butanol, sec-butanol, and tert-butanol;
[0012] The acid catalyst is selected from hydrochloric acid, nitric acid, and sulfuric acid.
[0013] The alkaline catalyst is selected from ammonia water;
[0014] Sol preparation is carried out in two steps:
[0015] A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the alcohol, 1 / 2 of the deionized water and acid catalyst, mix and stir evenly to prepare solution ①, add silicon source dropwise to solution ①, stir and hydrolyze at 40℃-50℃ for 2h-4h to obtain solution ②;
[0016] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of alcohol, the remaining deionized water and the alkaline catalyst to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0017] 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.003-0.006 mol / L. Finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier.
[0018] 3) Precast component molding: Inorganic fibers are added at a ratio of 0.1-0.25 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0019] The inorganic fiber is selected from one of glass fiber, basalt fiber, and quartz fiber;
[0020] 4) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; mix the sol containing SiO2 nanoparticles obtained in step 1) and the modifier obtained in step 2) evenly, and slowly pump it into the glue box under the conditions of -0.06 to -0.1 MPa and -5 to 0℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1-4 hours to ensure sufficient impregnation.
[0021] 5) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40℃ environment to wait for gelation. After gelation, add alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age in a 40℃ environment for 12-48 hours.
[0022] The alcohol mentioned is the same as the alcohol used in the sol preparation in step 1);
[0023] 6) Supercritical drying: The aged aerogel box is placed in a supercritical drying kettle for drying. The supercritical temperature is 260-280℃, the pressure is 8-12MPa, and the drying time is 4-8h to obtain the modified aerogel thermal insulation composite material.
[0024] 7) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 260-300℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material.
[0025] 8) Surface modification: 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDTES) was added to hexane and stirred for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L.
[0026] Then, the microwave-transparent thermal insulation aerogel material obtained in step 6) is placed in a container and then placed in a vacuum impregnation tank. The surface modifier is slowly pumped into the container at 40°C and -0.1 MPa vacuum to ensure thorough impregnation of the microwave-transparent thermal insulation aerogel material, and this process is maintained for 12 hours. After removal, it is heat-treated in a muffle furnace at 120°C for 24 hours to obtain a reusable microwave-transparent thermal insulation aerogel material. This reusable microwave-transparent thermal insulation aerogel material is then placed in a muffle furnace at 500°C for 2 hours. Even after 10 heat treatments, it still exhibits excellent hydrophobicity and wave-transmitting thermal insulation properties. The mass loss rate is 1.56-3.85%, the contact angle is 140.6°-160.5°, the mass moisture absorption rate is 0.98-1.90%, and it still maintains excellent wave-transmitting thermal insulation properties. After moisture absorption, the dielectric constant is 1.3-2.1, the dielectric loss tangent is 0.004-0.009 (10GHz), and the room temperature thermal conductivity is 0.020-0.030W / mK.
[0027] Furthermore, in step 2), the strong stirring condition has a rotation speed of 800-1000 rpm; the stirring condition has a rotation speed of 100-200 rpm; and the continuous stirring has a rotation speed of 100-200 rpm.
[0028] This invention also relates to a reusable microwave-transparent thermal insulation aerogel material, obtained by the above-mentioned preparation method. The reusable microwave-transparent thermal insulation aerogel material is heat-treated 10 times in a muffle furnace at 500°C for 2 hours, and still exhibits excellent hydrophobicity and microwave-transparent thermal insulation properties. The mass loss rate is 1.56-3.85%, the contact angle is 140.6°-160.5°, and the mass moisture absorption rate is 0.98-1.90%. Furthermore, it retains excellent microwave-transparent thermal insulation properties, with a dielectric constant of 1.3-2.1 after moisture absorption, a dielectric loss tangent of 0.004-0.009 (10GHz), and a room-temperature thermal conductivity of 0.020-0.030 W / mK.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] 1. The present invention discloses a method for preparing a reusable microwave-transparent thermal insulation aerogel material. This method employs an in-situ method combined with a surface modification method to prepare a superhydrophobic microwave-transparent thermal insulation aerogel material. The in-situ method features a simple and easily controllable formulation, without adding complex process steps. While ensuring the aerogel material is hydrophobic, it also introduces high-temperature resistant nano-inorganic oxide cerium oxide. Subsequently, PFDTES is grafted onto the surface through a surface modification method, further improving the hydrophobicity and temperature resistance. The combination of these two methods allows for controllable hydrophobic effects and a controllable formulation in the prepared aerogel material, resulting in good hydrophobic uniformity and superhydrophobicity both internally and externally. Simultaneously, it enhances the aerogel's temperature resistance and enables reusability.
[0031] 2. The reusable microwave-transparent thermal insulation aerogel material described in this invention, after being heat-treated 10 times in a muffle furnace at 500°C for 2 hours, still retains excellent hydrophobicity and microwave-transparent thermal insulation performance. Attached Figure Description
[0032] Figure 1 This is a process flow diagram of a method for preparing a reusable microwave-transparent thermal insulation aerogel material according to the present invention;
[0033] Figure 2 This is a diagram of the hydrophobic surface of the reusable microwave-transparent thermal insulation aerogel material prepared in Example 3 of the present invention after being heat-treated in a muffle furnace at 500°C for 2 hours 10 times.
[0034] Figure 3 This is a diagram of the surface of the microwave-transparent thermal insulation aerogel material prepared in Comparative Example 1 of the present invention after being heat-treated in a muffle furnace at 500°C for 2 hours 10 times. Detailed Implementation
[0035] The present invention will be further described in detail below through embodiments, but these embodiments should not be considered as limiting the present invention.
[0036] In the examples and comparative examples:
[0037] The contact angle was measured using a video contact angle meter.
[0038] The moisture absorption rate data were obtained according to GB / T 5480-2008.
[0039] The dielectric constant and dielectric loss tangent were obtained by measurement according to DqES423-2006.
[0040] The thermal conductivity data at room temperature were obtained by measurement in accordance with GB / T10295-2008.
[0041] Example 1:
[0042] A method for preparing a reusable microwave-transparent thermal insulation aerogel material includes the following steps:
[0043] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:0.75:3:5:1.8×10 -3 3.6×10 -2 Prepare the sol;
[0044] The silicon source is methyl orthosilicate;
[0045] The hydrophobic agent is PTMS;
[0046] The alcohol mentioned is methanol;
[0047] The acid catalyst is hydrochloric acid;
[0048] The alkaline catalyst is selected from ammonia water;
[0049] Sol preparation is carried out in two steps:
[0050] A. According to the molar ratio of the sol preparation, take all the mass of hydrophobic agent, 2 / 3 mass of methanol, 1 / 2 mass of deionized water and hydrochloric acid, mix and stir evenly to prepare solution ①, add methyl orthosilicate dropwise to solution ①, stir and hydrolyze at 40℃ for 2h to obtain solution ②;
[0051] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of methanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0052] 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.003 mol / L; finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier.
[0053] 3) Precast component molding: Inorganic fibers are mixed at a ratio of 0.20 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0054] The inorganic fiber is selected from glass fiber;
[0055] 4) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under -0.1MPa and 0℃ conditions. When the sol level exceeds the upper edge of the preform by 5-10mm, maintain the pressure in the vacuum impregnation tank for 2 hours to ensure thorough impregnation.
[0056] 5) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 12 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0057] 6) Supercritical drying: The aged aerogel box is placed in a supercritical drying kettle for drying. The supercritical temperature is 260℃, the pressure is 8MPa, and the drying time is 4h to obtain the modified aerogel thermal insulation composite material.
[0058] 7) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 260℃ for 2 hours to remove impurities, thereby obtaining a wave-transparent thermal insulation aerogel material.
[0059] 8) Surface modification: Add PFDTES to hexane and stir for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L; then place the microwave-transparent thermal insulation aerogel material prepared in step 6) into a container and place it in a vacuum impregnation tank. Under a vacuum of 40℃ and -0.1MPa, slowly pump the surface modifier into the container to ensure sufficient impregnation of the material and maintain it for 12 h; after removal, heat treat it in a muffle furnace at 120℃ for 24 h to obtain a reusable microwave-transparent thermal insulation aerogel material.
[0060] The resulting reusable microwave-transparent thermal insulation aerogel material has the following properties:
[0061] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 2.1%, the contact angle was 150.3°, and the mass moisture absorption rate was 1.90%. It still has excellent microwave-transparent thermal insulation performance. After moisture absorption, the dielectric constant is 2.1, the dielectric loss tangent is 0.004 (10GHz), and the thermal conductivity at room temperature is 0.020W / mK.
[0062] Example 2:
[0063] A method for preparing a reusable microwave-transparent thermal insulation aerogel material includes the following steps:
[0064] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:0.5:4:10:1.8×10 -3 3.6×10 -2 Prepare the sol;
[0065] The silicon source is selected from tetraethyl orthosilicate;
[0066] The hydrophobic agent mentioned is selected from PTES;
[0067] The alcohols mentioned are selected from ethanol;
[0068] The acid catalyst mentioned is selected from hydrochloric acid;
[0069] The alkaline catalyst is selected from ammonia water;
[0070] Sol preparation is carried out in two steps:
[0071] A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the ethanol, 1 / 2 of the deionized water and hydrochloric acid, mix and stir evenly to prepare solution ①. Add tetraethyl orthosilicate dropwise to solution ① and stir and hydrolyze at 40℃ for 2h to obtain solution ②.
[0072] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of ethanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0073] 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.005 mol / L; finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier.
[0074] 2) Precast component molding: Inorganic fibers are mixed at a ratio of 0.25 g / cm³. 3The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0075] The inorganic fiber mentioned is selected from quartz fiber;
[0076] 3) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under the conditions of -0.06MPa and -5℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1-4 hours to ensure sufficient impregnation.
[0077] 4) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 48 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0078] 5) Supercritical drying: The aged aerogel box was placed in a supercritical drying kettle for drying. The supercritical temperature was 280℃, the pressure was 12MPa, and the drying time was 8h to obtain the modified aerogel thermal insulation composite material.
[0079] 6) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 300℃ for 2 hours to remove impurities, thereby obtaining a wave-transparent thermal insulation aerogel material.
[0080] 7) Surface modification: Add PFDTES to hexane and stir for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L; then place the microwave-transparent thermal insulation aerogel material prepared in step 6) into a container and place it in a vacuum impregnation tank. Under a vacuum of 40℃ and -0.1MPa, slowly pump the surface modifier into the container to ensure sufficient impregnation of the material and maintain it for 12 h; after removal, heat treat it in a muffle furnace at 120℃ for 24 h to obtain a reusable microwave-transparent thermal insulation aerogel material.
[0081] The resulting reusable microwave-transparent thermal insulation aerogel material has the following properties:
[0082] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 1.8%, the contact angle was 160.5°, and the mass moisture absorption rate was 0.98%. It still has excellent microwave-transparent thermal insulation performance. After moisture absorption, the dielectric constant is 1.5, the dielectric loss tangent is 0.008 (10GHz), and the thermal conductivity at room temperature is 0.030W / mK.
[0083] Example 3:
[0084] A method for preparing a reusable microwave-transparent thermal insulation aerogel material includes the following steps:
[0085] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:0.5:4:15:1.8×10⁻⁶. -3 3.6×10 -2 Prepare the sol;
[0086] The silicon source is selected from tetraethyl orthosilicate;
[0087] The hydrophobic agent mentioned is selected from MTEOS;
[0088] The alcohols mentioned are selected from ethanol;
[0089] The acid catalyst mentioned is selected from nitric acid;
[0090] The alkaline catalyst is selected from ammonia water;
[0091] Sol preparation is carried out in two steps:
[0092] A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the ethanol, 1 / 2 of the deionized water and nitric acid, mix and stir evenly to prepare solution ①, add tetraethyl orthosilicate dropwise to solution ①, stir and hydrolyze at 50℃ for 4h to obtain solution ②;
[0093] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of ethanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0094] 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.005 mol / L; finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier.
[0095] 3) Precast component molding: Inorganic fibers are mixed at a ratio of 0.22 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0096] The inorganic fiber mentioned is selected from basalt fiber;
[0097] 4) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under conditions of -0.1MPa and -5℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1-4 hours to ensure thorough impregnation.
[0098] 5) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 48 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0099] 6) Supercritical drying: The aged aerogel box is placed in a supercritical drying kettle for drying. The supercritical temperature is 280℃, the pressure is 12MPa, and the drying time is 8h to obtain the modified aerogel thermal insulation composite material.
[0100] 7) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 300℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material.
[0101] 8) Surface modification: Add PFDTES to hexane and stir for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L; then place the microwave-transparent thermal insulation aerogel material prepared in step 6) into a container and place it in a vacuum impregnation tank. Under a vacuum of 40℃ and -0.1MPa, slowly pump the surface modifier into the container to ensure sufficient impregnation of the material and maintain it for 12 h; after removal, heat treat it in a muffle furnace at 120℃ for 24 h to obtain a reusable microwave-transparent thermal insulation aerogel material.
[0102] The resulting reusable microwave-transparent thermal insulation aerogel material has the following properties:
[0103] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 1.56%, the contact angle was 159.8°, and the mass moisture absorption rate was 1.01%. It still has excellent microwave-transparent thermal insulation performance. After moisture absorption, the dielectric constant is 1.3, the dielectric loss tangent is 0.006 (10GHz), and the thermal conductivity at room temperature is 0.022W / mK.
[0104] Figure 2 This is a diagram of the hydrophobic surface of the reusable microwave-transparent thermal insulation aerogel material prepared in Example 3 after being heat-treated 10 times in a muffle furnace at 500°C for 2 hours.
[0105] Example 4:
[0106] A method for preparing a reusable microwave-transparent thermal insulation aerogel material includes the following steps:
[0107] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:1:3:20:1.8×10 -3 3.6×10 -2 Prepare the sol;
[0108] The silicon source is selected from tetraethyl orthosilicate;
[0109] The hydrophobic agent mentioned is selected from MTEOS;
[0110] The alcohols mentioned are selected from isopropanol;
[0111] The acid catalyst mentioned is selected from hydrochloric acid;
[0112] The alkaline catalyst is selected from ammonia water;
[0113] Sol preparation is carried out in two steps:
[0114] A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the isopropanol, 1 / 2 of the deionized water and hydrochloric acid, mix and stir evenly to prepare solution ①. Add tetraethyl orthosilicate dropwise to solution ① and stir and hydrolyze at 50℃ for 4h to obtain solution ②.
[0115] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of isopropanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0116] 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.005 mol / L; finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier.
[0117] 3) Precast component molding: Inorganic fibers are mixed at a ratio of 0.18 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0118] The inorganic fiber mentioned is selected from basalt fiber;
[0119] 4) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under conditions of -0.1MPa and -5℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1 hour to ensure thorough impregnation.
[0120] 5) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 48 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0121] 6) Supercritical drying: The aged aerogel box was placed in a supercritical drying kettle for drying. The supercritical temperature was 260℃, the pressure was 8MPa, and the drying time was 4h; thus, the modified aerogel thermal insulation composite material was obtained.
[0122] 7) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 300℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material.
[0123] 8) Surface modification: Add PFDTES to hexane and stir for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L; then place the microwave-transparent thermal insulation aerogel material prepared in step 6) into a container and place it in a vacuum impregnation tank. Under a vacuum of 40℃ and -0.1MPa, slowly pump the surface modifier into the container to ensure sufficient impregnation of the material and maintain it for 12 h; after removal, heat treat it in a muffle furnace at 120℃ for 24 h to obtain a reusable microwave-transparent thermal insulation aerogel material.
[0124] The resulting reusable microwave-transparent thermal insulation aerogel material has the following properties:
[0125] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 3.85%, the contact angle was 140.6°, and the mass moisture absorption rate was 1.26%. It still has excellent microwave-transparent thermal insulation performance. After moisture absorption, the dielectric constant is 1.8, the dielectric loss tangent is 0.009 (10GHz), and the thermal conductivity at room temperature is 0.020W / mK.
[0126] Comparative Example 1:
[0127] The existing process for preparing hydrophobic aerogels, compared to Example 3, does not employ an in-situ method combined with surface modification to prepare reusable microwave-transparent thermal insulation aerogel materials. The steps are as follows:
[0128] 1) Sol preparation: Mix silicon source, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:4:5:1.8×10 -3 3.6×10 -2 Prepare the sol;
[0129] The silicon source is selected from tetraethyl orthosilicate;
[0130] The alcohols mentioned are selected from ethanol;
[0131] The acid catalyst mentioned is selected from nitric acid;
[0132] The alkaline catalyst is selected from ammonia water;
[0133] Sol preparation is carried out in two steps:
[0134] A. According to the molar ratio of the sol preparation, take 2 / 3 of the mass of ethanol, 1 / 2 of the mass of deionized water and nitric acid, mix and stir evenly to prepare solution ①, add tetraethyl orthosilicate dropwise to solution ①, and stir and hydrolyze at 40℃ for 2h to obtain solution ②;
[0135] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of ethanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0136] 2) Precast component molding: Inorganic fibers are mixed at a ratio of 0.22 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0137] The inorganic fiber mentioned is selected from basalt fiber;
[0138] 3) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under the conditions of -0.1MPa and -5℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 2 hours to ensure sufficient impregnation.
[0139] 4) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 48 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0140] 5) Supercritical drying: The aged aerogel box was placed in a supercritical drying kettle for drying. The supercritical temperature was 280℃, the pressure was 12MPa, and the drying time was 8h to obtain the modified aerogel thermal insulation composite material.
[0141] 6) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 260℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material.
[0142] The obtained aerogel wave-transparent thermal insulation material has the following properties:
[0143] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 0.56%, the contact angle was 0°, the mass moisture absorption rate was 30.6%, the microwave-transparent thermal insulation performance decreased significantly, the dielectric constant after moisture absorption was greater than 10, the dielectric loss tangent was 0.018 (10GHz), and the thermal conductivity at room temperature was 0.223W / mK.
[0144] Figure 3This is a diagram of the surface of the microwave-transparent thermal insulation aerogel material prepared in Comparative Example 1 after being heat-treated in a muffle furnace at 500℃ for 2 hours 10 times.
[0145] Comparative Example 2:
[0146] The preparation process of alumina aerogel differs from that in Example 3 in that it does not include the inorganic metal oxide cerium oxide and does not employ surface modification methods to improve the high-temperature resistance of the aerogel material. The steps are as follows:
[0147] 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:0.5:4:5:1.8×10 -3 3.6×10 -2 Prepare the sol;
[0148] The silicon source is selected from tetraethyl orthosilicate;
[0149] The hydrophobic agent mentioned is selected from MTEOS;
[0150] The alcohols mentioned are selected from ethanol;
[0151] The acid catalyst mentioned is selected from nitric acid;
[0152] The alkaline catalyst is selected from ammonia water;
[0153] Sol preparation is carried out in two steps:
[0154] A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the ethanol, 1 / 2 of the deionized water and nitric acid, mix and stir evenly to prepare solution ①. Add tetraethyl orthosilicate dropwise to solution ① and stir at 40℃-50℃ for 2h-4h to obtain solution ②.
[0155] B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of ethanol, the remaining deionized water and ammonia to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles;
[0156] 2) Precast component molding: Inorganic fibers are mixed at a ratio of 0.22 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation;
[0157] The inorganic fiber mentioned is selected from basalt fiber;
[0158] 3) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; after mixing the sol from step 1) and the modifier from step 2) evenly, slowly pump it into the glue box under conditions of -0.1MPa and -5℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1-4 hours to ensure thorough impregnation.
[0159] 4) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40°C environment to wait for gelation. After gelation, add an alcohol to the glue box to protect the gel surface from cracking. After sealing, continue to age at 40°C for 48 hours. The alcohol is the same as the alcohol used in the sol preparation in step 1).
[0160] 5) Supercritical drying: The aged aerogel box was placed in a supercritical drying kettle for drying. The supercritical temperature was 280℃, the pressure was 12MPa, and the drying time was 8h to obtain the modified aerogel thermal insulation composite material.
[0161] 6) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 300℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material.
[0162] The reusable microwave-transparent thermal insulation aerogel material was heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate was 2.34%, the contact angle was 109.8°, the mass moisture absorption rate was 12.4%, the hydrophobicity decreased, the dielectric constant after moisture absorption was greater than 10, the dielectric loss tangent was 0.012 (10GHz), and the thermal conductivity at room temperature was 0.075W / mK.
[0163] The results show that:
[0164] 1. By comparing Example 3 and Comparative Example 1, it is shown that the microwave-transparent thermal insulation aerogel composite material prepared by the in-situ method + surface modification method has excellent reusability. After repeated heat treatment at 500℃ for 2 hours, it still has superhydrophobicity, low dielectric constant and dielectric loss, and low thermal conductivity.
[0165] 2. By comparing Example 3 and Comparative Example 2, it is shown that the heat-insulating aerogel composite material prepared by the in-situ method + surface modification method and the one prepared by the in-situ method alone has better high-temperature resistance. Furthermore, the addition of inorganic oxide cerium oxide and the modification of PFDTES improve the reusability of the material at high temperatures.
[0166] The above are merely preferred embodiments of the present invention. The scope of protection of the present invention is not limited to the above embodiments. Various process solutions that are not substantially different from the concept of the present invention are all within the scope of protection of the present invention.
Claims
1. A method for preparing a reusable microwave-transparent thermal insulation aerogel material, characterized in that: Includes the following steps: 1) Sol preparation: Mix silicon source, hydrophobic agent, alcohol, deionized water, acid catalyst, and base catalyst in a molar ratio of 1:(0.25-1):(3-4):(5-20):1.8×10 -3 3.6×10 -2 Prepare the sol; The silicon source is selected from one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, and isopropyl orthosilicate. The hydrophobic agent is selected from one of phenyltrimethoxysilane, phenyltriethoxysilane, and methyltriethoxysilane; The alcohols mentioned are selected from one of methanol, ethanol, isopropanol, and tert-butanol; The acid catalyst is selected from hydrochloric acid, nitric acid, and sulfuric acid. The alkaline catalyst is selected from ammonia water; Sol preparation is carried out in two steps: A. According to the molar ratio of the sol preparation, take all the hydrophobic agent, 2 / 3 of the alcohol, 1 / 2 of the deionized water and acid catalyst, mix and stir evenly to prepare solution ①, add silicon source dropwise to solution ①, stir and hydrolyze at 40℃-50℃ for 2h-4h to obtain solution ②; B. According to the molar ratio of the sol preparation, take 1 / 3 of the mass of alcohol, the remaining deionized water and the alkaline catalyst to form solution ③, add solution ③ dropwise to solution ② to obtain a sol containing SiO2 nanoparticles; 2) Preparation of modifier: Dissolve 0.01 mol glucose and 0.015 mol acrylic acid in 80 ml deionized water under strong stirring; continue to add cerium nitrate hexahydrate under stirring to obtain a Ce(NO3)3 solution with a concentration of 0.003-0.006 mol / L. Finally, stir continuously for 5 h in a 30℃ water bath to obtain the modifier. The strong stirring conditions mentioned above involve a rotation speed of 800-1000 rpm; the stirring conditions mentioned above involve a rotation speed of 100-200 rpm; and the continuous stirring conditions mentioned above involve a rotation speed of 100-200 rpm. 3) Precast component molding: Inorganic fibers are added at a ratio of 0.1-0.25 g / cm³. 3 The fiber density is used to mold preforms, and the preforms are placed in a glue box to wait for impregnation; The inorganic fiber is selected from one of glass fiber, basalt fiber, and quartz fiber; 4) Impregnation: Place the glue box with the preform from the previous step into a vacuum impregnation tank; mix the sol containing SiO2 nanoparticles obtained in step 1) and the modifier obtained in step 2) evenly, and slowly pump it into the glue box under the conditions of -0.06~-0.1 MPa and -5~0℃. After the sol surface submerges the preform, maintain the pressure in the vacuum impregnation tank for 1-4 hours to ensure sufficient impregnation. 5) Gel and aging treatment: After impregnation, seal the glue box and place it in a 40℃ environment to wait for gelation. After gelation, add alcohol to the glue box to protect the gel surface and prevent cracking. After sealing, continue to maintain an environment of 40℃ for aging for 12-48 hours. The alcohol mentioned is the same as the alcohol used in the sol preparation in step 1); 6) Supercritical drying: The aged aerogel box is placed in a supercritical drying kettle for drying. The supercritical temperature is 260-280℃, the pressure is 8-12MPa, and the drying time is 4-8h to obtain the modified aerogel thermal insulation composite material. 7) Post-heat treatment: The prepared modified aerogel thermal insulation composite material is placed in an oven and heat-treated at 260-300℃ for 2 hours to obtain a wave-transparent thermal insulation aerogel material. 8) Surface modification: 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added to hexane and stirred for 10 min to obtain a surface modifier with a concentration of 0.01 mol / L; Then, the microwave-transparent thermal insulation aerogel material obtained in step 7) is placed in a container and then placed in a vacuum impregnation tank. Under a vacuum of -0.1 MPa at 40°C, the surface modifier is slowly pumped into the container to ensure that the microwave-transparent thermal insulation aerogel material is fully impregnated and maintained for 12 hours. After removal, it is heat-treated in a muffle furnace at 120°C for 24 hours to obtain a reusable microwave-transparent thermal insulation aerogel material. The reusable microwave-transparent thermal insulation aerogel material is heat-treated in a muffle furnace at 500°C for 2 hours 10 times and still has excellent hydrophobic effect and microwave-transparent thermal insulation performance. The mass loss rate is 1.56-3.85%; the contact angle is 140.6°-160.5°; the mass moisture absorption rate is 0.98-1.90%; the dielectric constant after moisture absorption is 1.3-2.1; the dielectric loss tangent at 10GHz is 0.004-0.009; and the thermal conductivity at room temperature is 0.020-0.030 W / mK.
2. A reusable microwave-transparent thermal insulation aerogel material, characterized in that: The reusable microwave-transparent thermal insulation aerogel material, prepared by the method described in claim 1, exhibits excellent hydrophobicity and microwave-transparent thermal insulation properties even after being heat-treated 10 times in a muffle furnace at 500°C for 2 hours. The mass loss rate is 1.56-3.85%; the contact angle is 140.6°-160.5°; the mass moisture absorption rate is 0.98-1.90%; the dielectric constant after moisture absorption is 1.3-2.1; the dielectric loss tangent at 10 GHz is 0.004-0.009; and the room temperature thermal conductivity is 0.020-0.030 W / mK.
Citation Information
Patent Citations
Silicon dioxide aerogel composite material and preparation method and application thereof
CN109336545A
Wave-transmitting, efficient and heat-insulating aerogel composite material and preparation method thereof
CN112851292A
